Coagulation and Bleeding Management in Pediatric Extracorporeal Membrane Oxygenation: Clinical Scenarios and Review - Hensch, Lisa A.; Hui, Shiu-Ki Rocky; Teruya, Jun (Frontiers in Medicine, 2019)
Extracorporeal membrane oxygenation (ECMO) is a life-saving procedure that requires careful coagulation management. Indications for ECMO continue to expand, leading to more complicated patients treated by ECMO teams. At our pediatric institution, we utilize a Coagulation Team to guide anticoagulation, transfusion and hemostasis management in an effort to avoid the all-to-common complications of bleeding and thrombosis. This team formulates a coagulation plan in conjunction with a multidisciplinary ECMO team after careful review of all available laboratory data as well as the patient's clinical status. Here, we present our general strategies for ECMO management in various clinical scenarios and a review of the literature pertaining to coagulation management in the pediatric ECMO setting.